Stratigraphic evidence of a Late Maeotian (Late Miocene) punctuated transgression in the Tanais Palaeobay (northern part of the Eastern Paratethys, South-West Russia) - Ruban, Dmitry (Geologos, 2010)
The Tanais Palaeobay was located in the northern periphery of the eastern Paratethys Sea during the Late Miocene. New data from the Safianovo section (Rostov Dome, South-West of Russia) confirm that skeletal limestones (coquinites) of the Merzhanovskaja Formation belong to the Congeria (Andrusoviconcha) amygdaloides navicula Zone of the upper Upper Maeotian (the Maeotian is a regional chronostratigraphic unit of the Upper Miocene). Correlation of reference sections of these Upper Maeotian deposits within the Rostov Dome results in pattern of the palaeobay transgression, which was punctuated. The relative importance of local and global controls on this trangsression is not yet clear.